ANALISIS PENGARUH RASIO KEUANGAN DAN PERTUMBUHAN ASET TERHADAP DEVIDEN PER SHARE PADA INDUSTRI WHOLE SALE AND RETAIL TRADE DI BURSA EFEK INDONESIA - Purwati, Mulia Indah (JUMANJI (JURNAL MANAJEMEN JAMBI), 2018)
This study is performed to examine the effect of Current ratio, Cash ratio, Debt to Total Equity (DER), Return on Investment (ROI), Earning per Share (EPS), Asset Growth  toward Dividend per Share (DPS) in industry Wholesale and Retail Trade that is listed in BEI. The objective of this study is to scale and analyze the effect of the company financial ratios performance (Current ratio, Cash ratio, Debt to Total Equity (DER), Return on Investment (ROI), Earning per Share (EPS), Asset Growth  toward Dividend per Share (DPS) in industry Wholesale and Retail Trade that is listed in BEI) over period 2009 - 2012. Sampling technique used here is purposive sampling on criterion (1) the company that trade their stocks in Bursa Efek Indonesia (BEI); (2) the company that represents their financial report per December 2009-2012; and (3) the company that continually share their dividend per December 2009-2012. The data is obtained based on Indonesian Capital Market Directory (ICMD 2012 and 2013) publication. It is gained sample amount of 15 companies from 30 companies those are listed in BEI. While simultaneously (Current ratio, Cash ratio, Debt to Total Equity (DER), Return on Investment (ROI), Earning per Share (EPS), Asset Growth) proof significantly influent DPS in Wholesale and Retail Trade industry in the level less than 5%. Predictable of the seven variables toward DPS is 68,90% as indicated by adjusted R square that is 68,90% while the rest 31,10% is affected by other factors is not included into the study model.